Paisagem em transformação: o eixo da MG 030 em Nova Lima/MG - Stefânia de Arújo Perna (2012)
The urban settlement in the natural environment and consequent landscape transformation has been a problem due to the incompatibility with environmental structures and the destruction of the landscape resources. Such situation also occurs in the area included in the sub-basin of Cardoso Stream, in the municipality of Nova Lima / MG. This space, located in the metropolitan city limits of Belo Horizonte, is structured by several types of urbanization: by the free-way MG-030, which links the municipalities of Belo Horizonte to Nova Lima, by the residential closed traditional plattings, by the areas of thickening and verticalization, by the mixed undertaking for single-family residence, multifamily residence and services, the areas occupied by mining diggings, important water sources, forests, brooks and by conservation units, which, allied with the rugged relief, allow scenes and places of important handscap and enviromental beauty. The plotting pattern wich takes place in the motorway axis, happens in a way different from the one wich occured in the beginning of the occupation.Considered initially as natural places for tourism, turned to a second residence, the plottings take shape of closed condominius, characterizad by the use of security systems and by the existence of spaces for public private use for the residents. As evolution of this last type of occupation, the process of verticalization and thickening of the condominiums, before marked by the horizontal and reduced urban occupation, beyond the acceleration of the verticalization process of consolidated areas. In a parallel way to this process, it takes place the increase of the residents number and the quest of road infrastructure, water supply and drain treatment, which hasn´t been adapted to the new reality. Add to this sight the elimination of planted areas and the incidence of erosive processes caused by urbanization in a landscape exposed to risks and to environment fragilities due to their high level of erosive liability and high hidraulic potentiality. We have established as an objective, the evaluation of manners of settlements and plotting, their positive and negative points in terms of occupation and the reflex of their implantation to the landscape. The analysis of the landscape transformation in the region doesn´t restric to the understanding of the ways the occupation forms, although it is the central question of this work. We have to bear in mind the logic of the metropolitan real estate market, the change of lifestyle, of consume and the speech about the escape from the city and the violence together with the search of the contact with nature. Also, the municipal management and its respective instruments, such as the plotting law, the use and occupation of the ground, the master plan, and others, beyond the decisions takings of the main political agents and the performance of private capital, the control of the production process are greatly important, so are the transformation and organization of this space.